Social networks and interactions in cities - Robert W. Helsley; Yves Zenou (Institute for the Study of Labor (IZA), 2011)
We examine how interaction choices depend on the interplay of social and physical distance, and show that agents who are more central in the social network, or are located closer to the geographic center of interaction, choose higher levels of interactions in equilibrium. As a result, the level of interactivity in the economy as a whole will rise with the density of links in the social network and with the degree to which agents are clustered in physical space. When agents can choose geographic locations, there is a tendency for those who are more central in the social network to locate closer to the interaction center, leading to a form of endogenous geographic separation based on social distance. Finally, we show that the market equilibrium is not optimal because of social externalities. We determine the value of the subsidy to interactions that could support the first-best allocation as an equilibrium and show that interaction effort and the incentives for clustering are higher under the subsidy program.
urn:nbn:de:101:1-201104113795
Keywords: D85; R14; Z13; 330; social networks; urban-land use; Bonacich centrality; Soziales Netzwerk; Soziale Beziehungen; Städtische Bodennutzung; Räumliche Verteilung; Entfernung; Theorie